(untitled) (International Journal of Engineering and Computer Science, 2015)
Well-structured website is not been design yet to facilitate effective user navigation.It has long been a challenge for developers. Mathematical model and two evaluation metrics using real data sets are to be discusses here. Here we also discusses the previous designed models and algorithms which are not so enough for effective user navigation. Developers design the website according to user’s behavior so that the most disoriented user can find their path easily.we are not reorganizing website,just by making substantial changes we are making website more useful. Our goal is to provide better navigation to user by proposed model.